Can Thyroid Gland Impact Your Fertility? - Ehab Tousson; Manal Elbandrawy (Current Overview on Disease and Health Research Vol. 2, 2022)
Thyroid disease is the second most common endocrine condition in human of childbearing age. It has since been largely confirmed that significant associations do exist between thyroid disorders and abnormalities of the reproductive system: both primary hyperthyroidism and hypothyroidism in males and females have been well documented to produce variable degrees of gonadal dysfunction (oligomenorrhea, amenorrhea, lack of sperms or infertility). Hyperthyroidism and hypothyroidism both affect testicular functions and influence neuroendocrine regulations over reproductive functions via the crosstalk between the hypothalamic-pituitary-thyroid axis and the hypothalamic-pituitary-gonadal axis. The alterations in the male reproductive hormonal milieu by thyroid hormones may lead to reduced testosterone levels and deterioration of semen quality. Thyroid disorders are involved in the control of menstrual cycle and in achieving infertility affecting the actions of follicular-stimulating hormone (FSH) and luteinizing hormone (LH) on steroid biosynthesis by specific triiodothyronine (T3) sites on oocytes, therefore affect all aspects of reproduction.